THE ADAPTIVE CITY OF MAJENE INFRASTRUCTURE STRATEGY TOWARDS COVID 19 PANDEMIC - Nur Adyla Suriadi (Universitas Sulawesi Barat, 2021)
Majene Regency is an education area in West Sulawesi that has greatly felt the impact of the PSBB that has been implemented, where technically the types of community activities are regulated in the Minister of Health Regulation (PMK) No.9 of 2020 concerning PSBB Guidelines as an Acceleration of Handling COVID-19, including dismissing schools and workplaces, restrictions on religious activities, restrictions on activities in public places, restrictions on socio-cultural activities, restrictions on transportation modes, and restrictions on other activities specifically related to aspects of defense and security, so there is a need for an adaptive infrastructure structuring strategy against the COVID-19 pandemic so that community activities remain can be done well but can also protect the community from the corona virus whichis troubling the community. The purpose of this study is to formulate a strategy for structuring the infrastructure of Majene City which isadaptive to the Covid 19 pandemic. Specifically, the objectives of this study are: (1) Analyzing infrastructure problems that are vulnerable to the spread of the Covid 19 virus, and (2) Formulating a strategy for structuring the infrastructure of Majene City which is adaptive to the covid pandemic 19. The research method used in the infrastructure structuring strategy that is adaptive to the Covid 19 pandemic is an exploratory descriptive analysis method with three stages of analysis techniques used, namely (1) descriptive analysis technique and character appraisal to identify infrastructure problems related to the distribution. corona virus, and (2) SWOT analysis techniques to formulate an adaptive infrastructure structuring strategy for the Covid 19 pandemic. The results achieved were an adaptive infrastructure structuring strategy for the Covid 19 pandemic.